Global strategies for implementing health financing equity – a state-of-the-art review of political declarations - Alexandre Nimubona; Innocent Yandemye; Chartière Nigaba; Beatrice Abura (International Journal for Equity in Health)
Abstract Background Implementing health financing equity plays a determining role in achieving Universal Health Coverage. For this reason, the global health community stated multiple political declarations to guide health financing equity implementation in countries. The aim of this study was to investigate the global strategies for implementing health financing equity that emerged from political declarations made before 2024. Methods Using a state-of-the-art review design, we identified the political declarations from the search of United Nations databases and the snowball search. We used textual and theoretical thematic analysis methods to extract the global strategies of health financing equity implementation that emerged from the political declarations. We grounded the global strategies in the existing practical framework – the Health Financing Progress Matrix of the World Health Organization. We employed a time-based descriptive analysis method to document the results. Quantitative information was used to shape the analysis. Results In total, 40 political declarations were included in the review. From these declarations emerged the strategies of targeted, selective, contributive, universal, claims, proportionate, experimental, united, and aggregated financing to implement health financing equity in countries. Thirty nine of the 40 political declarations that labelled the global health community from 1944 until 2023 placed more efforts on duplicating the prevailing strategies. The declarations, categorised into nine groups (target, unity, universality, selectivity, contribution, aggregation, claims, experience, and proportionality-oriented political declarations), were insistent to press countries effectively implement the strategies. Conclusion The political declarations proved to be the essential markers of the global health community’s efforts to raise the profile of health financing equity in countries. Although some of the global strategies that emerged from the political declarations have been shown promise in different countries, any global strategy is neither effective nor optimal for providing efficient and sustainable UHC in all countries. This lays the groundwork for careful management and adaptation of the global strategies to the diverse needs of the diverse population.